2017
DOI: 10.1063/1.4979977
|View full text |Cite
|
Sign up to set email alerts
|

Three-terminal quantum-dot thermal management devices

Abstract: We theoretically demonstrate that the heat flows can be manipulated by designing a three-terminal quantum-dot system consisting of three Coulomb-coupled quantum dots connected to respective reservoirs. In this structure, the electron transport between the quantum dots is forbidden, but the heat transport is allowed by the Coulomb interaction to transmit heat between the reservoirs with a temperature difference. We show that such a system is capable of performing thermal management operations, such as heat flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Dutta et al made a tunable heat valve gate by controlling the heat flow in a Kondo-correlated single-quantumdot transistor [20,21]. Zhang et al proposed a quantum thermal transistor based on three Coulomb-coupled quantum dots [22,23]. Jaliel et al experimentally realized a resonant tunneling energy harvester by connecting two quantum dots in series with a hot cavity [24].…”
Section: Introductionmentioning
confidence: 99%
“…Dutta et al made a tunable heat valve gate by controlling the heat flow in a Kondo-correlated single-quantumdot transistor [20,21]. Zhang et al proposed a quantum thermal transistor based on three Coulomb-coupled quantum dots [22,23]. Jaliel et al experimentally realized a resonant tunneling energy harvester by connecting two quantum dots in series with a hot cavity [24].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a very similar device was recently conceived as the first experimental autonomous Maxwell demon [24,25] and further studied theoretically [26]. More broadly, in the buoyant field of nanoscale thermoelectrics, other kinds of nano-devices have been recently examined, essentially for energy harvesting purpose, heat diode realization, or in the Maxwell demon context, both experimentally [27][28][29] and theoretically, [30][31][32][33][34][35][36][37][38][39]. A short pedagogical review can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Vidan et al presented an experimental realization of a triple quantum dot charging ratchet based on three tunnel-coupled quantum dots in the Coulomb blockade regime [34]. Recent experimental studies have shown that a triple quantum dot with triangular geometry can simultaneously measure electronic transport along two different paths [37] and the effect of interactions between the charge flowing through the two different paths have also been analyzed [38].When consider three capacitively coupled quantum dots with triangular geometry in the Coulomb-blockade regime, the electron transport between the quantum dots is forbidden, but the heat transport is allowed by the Coulomb interaction [40]. In this respect, the triple quantum dots offer the possibility of analyzing new fascinating properties which are not presented in double quantum-dot systems.…”
mentioning
confidence: 99%
“…When consider three capacitively coupled quantum dots with triangular geometry in the Coulomb-blockade regime, the electron transport between the quantum dots is forbidden, but the heat transport is allowed by the Coulomb interaction [40]. In this respect, the triple quantum dots offer the possibility of analyzing new fascinating properties which are not presented in double quantum-dot systems.…”
mentioning
confidence: 99%